Relation between Fe-oxides transformation and phosphorus adsorption in the oxic and anoxic layers of two paddy soils as affected by flooding - ZHANG Yong-song; LIN Xian-yong (浙江大学学报. 农业与生命科学版)
The changes of total reducing substances (TRS), oxalate-extractable Fe (Feo), dithionite-citrate-bicarbonate extractable Fe (FeDCB) and phosphorus adsorption (P adsorption) in oxic and anoxic layers of two paddy soils during 6-week flooding were examined under laboratory conditions. It was found that TRS, Feo, and P adsorption in fresh samples were sharply increased by flooding, and significantly higher in anoxic layers than in oxic layers of the submerged soils. The significant correlation (at 1% level) between TRS, Feo and P adsorption suggested that the substantial increase of P adsorption caused by flooding was ascribed to the reducing process of soil Eh resulting from flooding, transformation of FeDCB to Feo, and poor crystallinity of soil iron oxide induced by low Eh.